German Cooperation Programs and Sustainable Agribusiness Development in Nigeria - Musa Zakari; Lugud Mumen (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Sustainable agribusiness development has become a major priority for improving food security, productivity, competitiveness, climate resilience, and rural economic growth. Specific Background: In Nigeria, the German Agency for International Cooperation (GIZ) has implemented intervention programmes focusing on capacity-building, value-chain training, agricultural innovation, and market-linkage support to address persistent agribusiness challenges. Knowledge Gap: Despite the scale of these interventions, limited empirical evidence exists regarding their direct contribution to sustainable agribusiness development in Nigeria. Aims: This study evaluated the contribution of GIZ intervention programmes to sustainable agribusiness development, with particular emphasis on capacity-building, value-chain training, agricultural innovation, and market-linkage support. Results: Using survey and documentary research designs, data were collected from agribusiness stakeholders, farmers, cooperative leaders, and extension officers. Findings revealed that capacity-building and value-chain training significantly improved sustainable agribusiness productivity (p=0.000), while agricultural innovation and market-linkage support significantly increased agribusiness competitiveness (p=0.000). The regression model explained 61.0% of the variation in sustainable agribusiness development. Novelty: The study provides direct empirical evidence linking GIZ-specific intervention programmes with sustainable agribusiness outcomes in Nigeria. Implications: The findings support the expansion of capacity-building initiatives, innovation support, market-linkage mechanisms, and climate-smart agricultural interventions as strategies for promoting sustainable agribusiness development and agricultural transformation in Nigeria. Keywords: Agribusiness Development, Capacity Building, Agricultural Innovation, Market Linkage Support, Sustainable Agriculture Key Findings Highlights Capacity-building activities strengthened productivity among agribusiness beneficiaries. Innovation-oriented interventions supported stronger competitive performance. Development cooperation initiatives contributed to long-term agricultural transformation.